Dimensions of Public Services Management Program in Increasing Employee Performance to Realize Service Effectiveness (Case Study: Garut Regency Environmental Service) - Widaningsih, M.; Rulandari, Novianita; Muharam, Husni (Budapest International Research and Critics University, 2021)
Public services running so far still have weaknesses; there are still many complaints from the public. Therefore we researched to examine and analyze the influence of government service program management on employee performance in realizing the effectiveness of achieving public services. This research uses an explanatory method with a survey technique. The research population is employees at the Department of the Environment. The sampling technique uses a census. Methods of data collection using observation, interviews, questionnaires, and documentation studies. Methods of data analysis using the method of path analysis (path analysis). The study results indicate that the management of government service programs is not optimal because there are still problems in determining staff, preparing the implementing structure, and distributing tasks. In employee performance, there are still problems of independence in decision making, work speed, and cooperation. On the effectiveness of achieving government services, there are still problems achieving length of service time, quality of service, and completeness of service. Thus, based on the findings in this study, there are several things that the authors suggest, namely: first, the Regional Government Assistants improve guidance to service providers related to service program management. Second, improve coaching for employees to improve employee abilities. Third, employees should be able to improve their ability to use technology and innovate to carry out services quickly. Fourth, increasing the availability of service facilities through proposals to the district government to increase the service budget.